Measurement of Soil Thermal Conductivity as A Basis for Selecting Soil Types for Photovoltaic Passive Cooling Systems - Abdurrohman; Rindi Wulandari (Al-Makki Publisher, 2026)
This study aims to measure and analyse the thermal conductivity of clay and sandy soils as potential media for passive cooling systems in photovoltaic modules. A quantitative experimental approach was employed using the Transient Line Heat Source (TLS) method, which utilises the temperature response over time due to a linear heat source. The measurement system was developed using an ESP32 microcontroller integrated with a DS18B20 temperature sensor capable of real-time data acquisition. The results indicate that the system operates in an integrated manner and produces stable data for thermal conductivity calculations. The thermal conductivity of clay soil was found to be 1.133 W/mK at a moisture content of 74.25%, while coastal sandy soil exhibited a higher value of 1.595 W/mK at a moisture content of 81.25%. Sandy soil demonstrated approximately 40.78% higher heat transfer capability compared to clay soil. These findings suggest that, in addition to soil type, moisture content plays a significant role in determining thermal conductivity. Soils with higher moisture content therefore hold greater potential as passive cooling media for enhancing the efficiency of photovoltaic systems.